Leveraging Textual Paralanguage and Consumer–Brand Relationships for More Relatable Online Brand Communication: A Social Presence Approach. Issue 1 (2nd January 2020) - Hayes, Jameson L.; Britt, Brian C.; Applequist, Janelle; Ramirez, Artemio; Hill, Jayme
Abstract: The recent proliferation of social Web applications has facilitated an array of new customer engagement behaviors. Creating social presence in brand communication is key to creating positive outcomes for brands. Present research integrates social presence theory and the consumer–brand relationship (CBR) perspective in examining how the use of textual paralanguage (TPL; e.g., emojis and emoticons) and CBRs can be leveraged to enhance message relatability in the context of responding to product reviews. A 2 (CBR strength) × 3 (TPL) online experiment is conducted. Findings show that TPL use increases the social presence of brand messages, leading to more positive attitude toward the brand, greater purchase intention, and the strengthening of brand relationships. Further, while CBR strength did not influence social presence of responses, actively engaging with consumers increases purchase intention and significantly strengthens weak brand relationships.